PENGARUH IMPELENTASI KEBIJAKAN SERTIFIKASI GURU TERHADAP KINERJA GURU SMA DI KABUPATEN DONGGALA - Angriani, Angriani (Katalogis, 2017)
This study aims to identify and analyze; (1) the effect of policy implementation of teacher certification simultaneously on the performance of high school teachers in Donggala; (2) the effect of policy implementation of teacher certification partially on the performance of a high school teacher in Kabupatenh Donggala. The theory used in the variable policy implementation certification (X) is the theory of George Edward III who explains that there are four (4) dimensions in policies teacher certification, these dimensions are (1) communication, (2) resources, (3) disposition, and (4) a bureaucratic structure. While the variable performance of teachers (Y) using the theory of TR Mitchell stating that there are five (5) dimensions to measure teacher performance, namely (1) the quality of work, (2) timeliness, (3) initiatives, (4) ability and (5) communication. Data were analyzed using multiple linear regression. The results showed; (1) the magnitude of the effect of policy implementation of teacher certification simultaneously on the performance of high school teachers in Donggala simultaneously (together) is determined by the communication, resources, disposition and bureaucratic structure. Great influence policy implementation certification of teachers on teacher performance is 63.2% with the level of relations between the implement teacher certification policies with teacher performance is